Genética textual: um estudo sobre os tipos e as funções das rasuras em manuscritos de alunos recém-alfabetizados - Oliveira, Dayane Rocha de (2022)
This article analyzes the erasures in textual production processes in the classroom in which pairs of students (7 years old) who collaboratively write their first texts participate. Supported by Textual Genetics, we will present and delimit the erasure functions proposed by Grésillon (1991, 2007), Biasi (1996), Willemart (1993, 1999) and Fabre (1986), as well as the erasure types in Felipeto (2019) and Calil (2019). We chose as analysis categories the types and functions of the erasures, aiming: a) analyze and classify erasures in the texts of students from the 2nd year of elementary school in Brazil and Portugal, whose data were collected through the Ramos System; b) compare and discuss nomenclatures, types and functions of existing erasures, in view of variations in the area; and, c) finally, to verify which ones occur most, comparing Brazilian students with Portuguese students. The protocol for data collection in both countries was the same and the results showed that the most used functions are substitution and suppression. Regarding the types, the most common were: spelling, graphics, discursive textual, punctuation, anticipation, syntactic and accentuation, as the students worked and reflected on the text produced.